Security for Mobile Agents: Trust Estimate for Platforms - Razouki Hassan; Hair Abdellatif (Institute of Advanced Engineering and Science, 2015)
The mobile agent has been seen as a promising distributed computing technology. The mobility characteristic of mobile agent makes it to travel often in open network. In this scenario, it is obvious that the mobile agents are vulnerable to various security threats. Protecting free-roaming mobile agents from malicious host and from other mobile agents has drawn much attention in recent years. The protection of mobile agents is considered as one of the greatest challenges of security, because the platform of execution has access to all the components of the mobile agent. In this paper, we present a new architecture paradigm of mobile agents, which allows the separation of the implementation tasks of the agent and its security mechanisms. Our approach is based on using two strategies of adaptation to adapt the mobile agent security at runtime, depending on the sensitivity of the services required to perform the duties of the agent and the degree of confidence of the visited platforms.